Analysis Of The Effect Of Gender And Poverty In The Home Industry Of Butija Woven Fabrics In The District Of Taopa West, Parigi Moutong Central Sulawesi Province - Sitti RAHMAWATI; Chairil ANWAR; Khaeruddin THAHA; Suparman SUPARMAN; Aris MUHAMAD (Journal of Tourism Economics and Policy, 2023)
Poverty in women is more complex when faced with other problems, such as low education, low asset ownership and control, and a larger female population than male population. Women of West Taopa use Butija sarong weaving to produce goods and services. This study aims to determine production costs, income, and the role of gender in Taopa Barat District, Parigi Moutong Regency's butija woven fabric industry. The population and sample consisted of 28 groups of Butija Weaving Industry craftsmen. Data collection techniques used primary data through interview guidelines in the form of a questionnaire (list of questions) to respondents. Data analysis was carried out descriptively, with an explanatory research type. The research location was Taopa Barat Village, Taopa Barat District Parigi Moutong. Based on the income analysis of the Butija woven sarong craft business with a total operational cost of Rp. 37,926,500 consisting of fixed and variable costs, and net income is gross revenue of Rp114.300.000, which is reduced by the total production cost of Rp37,926,500. Net income per month is Rp8,864,500 or Rp106,373,500. The wife's contribution to family income in the Butija weaving craft industry plays a significant role in meeting the family's economic needs, especially the role of women who own a Butija weaving craft group business in West Taopa, Parigi Moitong Regency.